Sense of Coherence and Mental Health in College Students After Returning to School During COVID-19: The Moderating Role of Media Exposure - Li, Man; Xu, Zhansheng; He, Xinyue; Zhang, Jiahui; Song, Rui; Duan, Wenjin; Liu, Tour; Yang, Haibo (Frontiers in Psychology, 2021)
The COVID-19 epidemic not only threatens people's physical health, but also affects their mental health in the long term. Although people had returned to work and school, they are closely monitoring the development of the epidemic and taking preventive measures. Therefore, this study conducted an online survey on 424 college students returning to school around May 2020. We used Media exposure scale, Sense of Coherence Scale (SOC-13) and Depression-Anxiety-Stress Scale (DASS-21) to explore the relationship between media exposure, SOC and mental health in college students after returning to school. The results showed that (1) negative epidemic information exposure, rather than positive epidemic information exposure, was significantly associated with depression, anxiety, and stress. (2) SOC was also associated with depression, anxiety, and stress. (3) The effect of SOC on depression was modified by negative epidemic information exposure. With the increase of negative epidemic information exposure, the predictive effect of SOC on depression is increasing gradually. The results suggest that a high SOC plays a certain protective role in the adaptation of college students in the post-epidemic period. For most people, we should pay more attention to positive information to maintain mental health.